Edward Thomas' 'Romanticism' - Brooks, Martin (2020)
This is a thesis about the links between Edward Thomas’ (1878-1917) criticism and his poetry. It identifies two major strands of Thomas’ criticism which inform his poetry: his critical ideas of what different Romantic-period poets had accomplished; and his specifically late nineteenth- and early twentieth-century ‘Romantic’ literary theory of what poetry ought to be. In doing so, this thesis is the first to demonstrate the importance these parts of Thomas’ criticism have to his practice as a poet. It demonstrates how they enabled Thomas to develop the particular ideas of what poetry is and does which make him distinctive among early twentieth-century poets. This thesis is in four chapters. Chapter One sketches the critical background to the thesis. It documents the longstanding critical debate of how Thomas’ poetry might fit within narratives of Modernism and Romantic-period poetry and then proceeds to outline the cultural links which make Thomas’ literary theory ‘Romantic’. Three subsequent chapters each focus on the links between Thomas’ criticism of a different Romantic-period poet, his own poetry, and the wider context of late nineteenth- and early twentieth-century poetry. Chapter Two discusses Thomas’ work on and after Samuel Taylor Coleridge (1772-1834). It shows how Thomas’ unique critical approach to Coleridge forms a part of his own poetry which distances him from poets who became associated with Modernism and from other early twentieth-century writers whose jingoistic attitudes were amplified by the First World War. Chapter Three concerns connections between Thomas’ poetry and his criticism on Percy Bysshe Shelley (1792-1822). It shows that Thomas used his writing on Shelley to work out a theory of how poets should use symbols in their work. It explores how Thomas’ subsequent use of this theory in his own poetry differentiates him from French Symbolist poets and their anglophone admirers. The fourth chapter discusses the impact of Thomas’ criticism of John Keats (1795-1821) on how his own poetry represents individuals losing their identities. The chapter shows that Thomas’ uniqueness as a Keats critic generated the critical positions that differentiate his poetry from how some key Modernist poets were depicting individual identity as unstable. In using these four chapters to explore Thomas’ poetry in relation to his criticism and literary theory, this thesis provides a new account of his complex connections to the development of English poetry in the late nineteenth and early twentieth centuries.